Application of The Argument Driven Inquiry (ADI) Model Using Interactive E-LKPD to Improve Students' Argumentation Skills - Wibowo, Aldi Alfiansyah; Evi Roviati; Novianti Muspiroh (Universitas Islam Negeri Walisongo Semarang, 2024)
Most students are not skilled in writing scientific arguments, have not expressed opinions accompanied by relevant data, learning uses teacher-centered discussion methods but is still not optimal, and teachers have never applied learning to improve students' argumentation skills. So, an alternative for improving students' argumentation skills is to use the Argument Inquiry (ADI) model, a recommendation for a 21st-century skills inquiry learning model that can improve students' argumentation skills. This research aims to analyze student activities in implementing the Argument-Driven Inquiry (ADI) model using Interactive E-LKPD, to analyze the increase in argumentation skills in students who apply the ADI model using Interactive E-LKPD and students who do not apply the ADI model using E-LKPD Interactive, and to analyze how students respond after learning by implementing the ADI model assisted by Interactive E-LKPD. This research was carried out at Al-Azhar 5 Cirebon Islamic High School. With a class X population, the samples are classes X.3 and X.1. Research on student activities during 3 meetings showed that the experimental class obtained the highest average score in the double-blind peer review syntax. The students' lowest activity during the learning process was the syntax for revising peer review reports. There is a significant difference in the increase in students' argumentation skills for the better after implementing the ADI learning model compared to students who did not apply the ADI learning model. The response of students who applied the ADI model assisted by Interactive E-LKPD showed a positive response